Optical nanoscopy of tissue sections - Villegas Hernandez, Luis Enrique (UiT Norges arktiske universitet, 2018)
The study of organ tissues, namely, histology, is essential for clinical medicine, as it allows the identification of a wide range of diseases. Traditionally, two major techniques, optical and electron microscopy, have been used for morphological observation of tissue sections. Optical microscopy (OM) allows for fast-acquisition high-throughput imaging, at the expense of diffraction-limited resolution (~200nm), whereas electron microscopy (EM) provides with sub-diffraction resolution at low throughput. Routine histological studies require visualization of large field-of-view (FOV) at high throughput. Pathologies such as nephrotic syndrome, brain neoplasms, neuromuscular disorders, to name just a few, require sub-diffraction resolution, placing EM as the primary technique for its clinical diagnose. In recent years, a new discipline of super-resolution microscopy (SRM), also referred to as optical nanoscopy, has emerged, which achieves sub-diffraction resolution at a faster throughput than EM, allowing for visualization of biological processes at nanoscopic scale. To date, benefits of SRM have been exploited mainly on cellular studies, yet they remain practically unexplored for histological analysis. This master project aimed to image, for the first time, histological samples using two super-resolution optical systems at the UiT – The Arctic University of Norway, namely, the commercial OMX microscope, and the waveguide chip-based microscope setup. Formalin-fixed paraffin-embedded (FFPE) and cryo-preserved tissue sections from human and non-human origin were fluorescently labeled and imaged on the OMX using super-resolution structure illumination microscopy (SIM) and diffraction-limited deconvolution microscopy (DV). Similarly, histological samples were imaged on the waveguide chip-based microscope setup using diffraction-limited total internal reflection fluorescent (TIRF) microscopy. Furthermore, a correlative light-light microscopy has been performed, to compare the three previously mentioned microscopy ...